Enhancing ethanol dehydration through optimized WO3 loading on activated carbon and montmorillonite clay catalysts - Chaowat Autthanit; Sasiradee Jantasee; Jirayu Liewchalermwong; Narathip Thubthun; Supachai Jadsadajerm; Piyasan Praserthdam; Bunjerd Jongsomjit (Carbon Resources Conversion)
The objective of this study is to investigate the utilization of tungsten oxide (WO3) supported on natural materials, including activated carbon (AC) and montmorillonite clay (MMT), for the catalytic dehydration of ethanol. This study addresses the growing demand for sustainable chemical processes that produce key intermediates, such as ethylene and diethyl ether, from renewable resources. The research examined the effect of varying WO3 loadings on catalyst performance using the incipient wetness impregnation method. The physicochemical properties of catalysts were elucidated through a variety of characterization techniques. The results revealed that MMT supports exhibited a more significant enhancement in catalytic efficiency compared to AC when loaded with W. This superior performance is attributed to MMT’s unique layered structure, enabling efficient dispersion of tungsten species and optimized acid site distribution. The structural properties of the support and the higher density of weak acid sites were found to significantly influence catalytic activity. The 13.5WMMT catalyst demonstrated remarkable dual functionality, achieving 42.63 % diethyl ether yield at 250 °C and 96.73 % ethylene yield at 400 °C. In contrast, the 13.5WAC catalyst produced only 22.30 % diethyl ether yield at 300 °C and 77.02 % ethylene yield at 400 °C. The study not only underscores the significance of metal loading and support type in achieving superior catalytic performance, but also highlights the exceptional potential of MMT as a promising candidate for sustainable and efficient ethanol dehydration processes.